Choose your wow! : a disciplined agile approach to optimizing your way of working - Ambler, Scott W., 1966-; Lines, Mark, 1964- (Project Management Institute, Inc., 2022)
"Hundreds of organizations around the world have already benefited from Disciplined Agile Delivery (DAD). Disciplined Agile® (DA) is the only comprehensive tool kit available for guidance on building high-performance agile teams and optimizing your way of working (WoW). As a hybrid of the leading agile, lean, and traditional approaches, DA provides hundreds of strategies to help you make better decisions within your agile teams, balancing self-organization with the realities and constraints of your unique enterprise context"-- Provided by publisher.
Keywords: Agile software development.; Project management.; Teams in the workplace.; elektronické knihy; electronic books